Polymer, preparation method and application thereof, self-repairing antibacterial photocuring coating composition, preparation method and application thereof, and product

By using polymers with polyurethane segments, functional structural units and acrylate end group, combining disulfide bond chain extenders and quaternary ammonium salt segments, the existing photocuring coatings have short service life, poor antibacterial effect, and self-causing The problems of low repair rate and long curing time have achieved efficient self-healing and antibacterial functions.

CN119431714AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310961568.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

The existing photocured coatings have short service life, poor antibacterial effect, low self-repair rate and long curing time, making it difficult to maintain antibacterial properties and mechanical strength on the surface of public goods for a long time.

Method used

Using polymers containing polyurethane segments, functional structural units and acrylate endpoint groups, their structure is determined through nuclear magnetic and infrared analytical means, combining disulfide bond chain extenders and quaternary ammonium salt segments to achieve self-healing of the coating film. and antibacterial function.

Benefits of technology

The service life, antibacterial effect, self-repair rate and photocuring time of the coating are improved, and a self-repair antibacterial photocuring coating with excellent performance is formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004371902110000022
    Figure BDA0004371902110000022
  • Figure BDA0004371902110000031
    Figure BDA0004371902110000031
  • Figure BDA0004371902110000052
    Figure BDA0004371902110000052
Patent Text Reader

Abstract

The invention relates to the technical field of organic photocuring, in particular to a polymer, a preparation method and application of the polymer, a self-repairing antibacterial photocuring coating film composition, a preparation method and application of the self-repairing antibacterial photocuring coating film composition and a product of the self-repairing antibacterial photocuring coating film composition. The polymer comprises a polyurethane chain segment, a functional structure unit and an acrylate end-capping group, the functional structural unit comprises a structural unit A with-S-S-groups and a structural unit B shown as a formula (1); r is a copolymer chain containing a structural unit C as shown in a formula (2), a structural unit D as shown in a formula (3) and a structural unit E from monoolefine. The polymer provided by the invention comprises a reversible covalent bond disulfide bond, a quaternary ammonium salt chain segment and a polyurethane chain segment; the disulfide bond can partially or completely recover the mechanical property and integrity of the polymer under the stimulation of external conditions such as light, heat or acid-base, and can realize repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic photocuring, and in particular to a polymer and a preparation method and application thereof, a self-repairing antibacterial photocuring coating composition and a preparation method and application thereof, and a product thereof. Background Art

[0002] Polyurethane is a general term for a class of polymer compounds containing carbamate units in the main chain. It is a multi-block polymer formed by the gradual polymerization of polyols, small molecule chain extenders and polyisocyanates. Polyols constitute the soft segment, small molecule chain extenders and polyisocyanates constitute the hard segment. The molecular structure and physical and chemical properties of polyurethane can be effectively controlled by adjusting the components and proportions in the soft and hard segments. Ordinary polyurethane coatings do not have the ability to resist microbial or bacterial erosion during actual use. Coatings contaminated with bacteria will cause damage to human health and materials. Therefore, polyurethane-based antibacterial coatings have been widely used. Most polyurethane-based antibacterial coatings on the market belong to the type of external antibacterial agents, that is, small molecule antibacterial agents are mixed into the coating by physical blending or surface coating, and then the antibacterial function is achieved by the release or contact killing of the bactericide. However, this type of antibacterial coating has great limitations. Its composite antibacterial agent may migrate, resulting in a decrease in antibacterial performance or environmental pollution. Therefore, self-antibacterial polyurethane antibacterial coatings that use chemical modifications such as graft copolymerization or block copolymerization to polymerize antibacterial groups into the polyurethane main resin through chemical bonds are becoming more and more popular.

[0003] At the same time, UV-curable coatings are widely used in the coating field due to their advantages such as environmental protection, energy saving, high efficiency, and fast film-forming rate. However, in actual use, the coatings usually have microcracks, scratches, or even breakage due to friction, collision, etc. This weakens the dimensional stability and mechanical strength of the coatings to varying degrees. Therefore, combining the bactericidal function with the self-repairing function and developing an antibacterial coating with self-repairing ability is critical to ensuring antibacterial performance and improving service life. However, there are currently few reports on self-repairing antibacterial coatings, the preparation process is relatively complicated, and the self-repairing conditions are relatively harsh.

[0004] Therefore, it is necessary to invent a new photocurable coating. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of short service life, poor antibacterial effect, low self-repair rate and long curing time of photocurable coatings in the prior art, and to provide a polymer and its preparation method and application, a self-repairing antibacterial photocurable coating composition and its preparation method and application and products. The self-repairing antibacterial photocurable coating prepared by the polymer has the advantages of long service life, good antibacterial effect, high self-repair rate and short photocuring time, and can be used in surface finishing of public goods.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a polymer, which comprises a polyurethane segment, a functional structural unit and an acrylate end-capping group; the functional structural unit comprises a structural unit A having a -SS- group and a structural unit B represented by formula (1);

[0007] R2 is a C1-C6 straight chain or branched alkyl group, R1 and R3 are each independently a structure represented by the general formula -O-Z1* or -NH-Z2*, and Z1 and Z2 are each independently a C1-C6 straight chain or branched alkylene group,

[0008] R is a copolymer chain containing a structural unit C represented by formula (2), a structural unit D represented by formula (3) and a structural unit E derived from a monoolefin,

[0009]

[0010] R 1 is selected from a C1-C6 straight or branched alkylene group, R 2 is selected from -H or a C1-C6 straight or branched alkyl group, * is the position connecting to the N element in formula (1); X is selected from F, Cl, Br or I.

[0011] The structure of the above-mentioned polymer can be determined by combining nuclear magnetic resonance and infrared analysis, or by feeding materials during preparation.

[0012] A second aspect of the present invention provides a method for preparing a polymer, the method comprising the following steps:

[0013] (1) in the presence of a catalyst, polyisocyanate and oligomer polyol are subjected to polycondensation reaction to generate a solution A containing polyurethane;

[0014] (2) copolymerizing solution A, an embedded copolymer and a disulfide bond extender to obtain a polymer precursor; the embedded copolymer contains a structural unit D represented by formula (3), a structural unit F represented by formula (5) and a structural unit E derived from a monoolefin,

[0015]

[0016] (3) subjecting the polymer precursor and the end-capping agent to an end-capping reaction to obtain a polymer;

[0017] R1, R2, R3, R, R 2 The definition is the same as that in claim 1.

[0018] The third aspect of the present invention provides a polymer obtained by the preparation method of the present invention.

[0019] A fourth aspect of the present invention provides a self-repairing antibacterial photocurable coating composition, which contains the polymer described in the present invention.

[0020] A fifth aspect of the present invention provides an application of the polymer described in the present invention in a self-repairing antibacterial cured coating.

[0021] A sixth aspect of the present invention provides a method for preparing a self-repairing antibacterial photocurable coating film, the preparation method comprising the following steps:

[0022] (1) mixing a polymer, a reactive diluent, and a photoinitiator to obtain a mixture A;

[0023] (2) Curing the mixture A to obtain a self-repairing antibacterial photocured coating.

[0024] The seventh aspect of the present invention provides a self-repairing antibacterial photocured coating film prepared by the preparation method described in the present invention.

[0025] An eighth aspect of the present invention provides an application of the self-repairing antibacterial photocuring coating film described in the present invention in surface finishing of public goods.

[0026] A ninth aspect of the present invention provides a product having the self-repairing antibacterial photocured coating film of the present invention on its surface.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] The polymer provided by the invention comprises a reversible covalent disulfide bond, a quaternary ammonium salt segment and a polyurethane segment; the disulfide bond can partially or completely restore the mechanical properties and integrity of the polymer itself under the stimulation of external conditions such as light, heat or acid and alkali, and can achieve repair; the quaternary ammonium salt enables the polymer to have good bactericidal performance and the quaternized stability of the polymer of the invention is high; the polyurethane system has strong versatility, excellent and adjustable performance, and has a variety of molecular structures with different structures and performances.

[0029] The photocurable coating prepared by the polymer provided by the invention has simple process, is green and environmentally friendly, has strong practicality and strong antibacterial property. DETAILED DESCRIPTION

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] The first aspect of the present invention provides a polymer, the polymer comprising a polyurethane segment, a functional structural unit and an acrylate end-capping group; the functional structural unit comprises a structural unit A having a -SS- group and a structural unit B represented by formula (1);

[0032] R2 is a C1-C6 straight chain or branched alkyl group, R1 and R3 are each independently a structure represented by the general formula -O-Z1* or -NH-Z2*, and Z1 and Z2 are each independently a C1-C6 straight chain or branched alkylene group,

[0033] R is a copolymer chain containing a structural unit C represented by formula (2), a structural unit D represented by formula (3) and a structural unit E derived from a monoolefin,

[0034]

[0035] R 1 is selected from a C1-C6 straight or branched alkylene group, R 2 is selected from -H or a C1-C6 straight or branched alkyl group, * is the position connecting to the N element in formula (1); X is selected from F, Cl, Br or I.

[0036] The polymer provided by the invention comprises a reversible covalent disulfide bond, a quaternary ammonium salt segment and a polyurethane segment; the disulfide bond can partially or completely restore the mechanical properties and integrity of the polymer itself under the stimulation of external conditions such as light, heat or acid and alkali, and can achieve repair; the quaternary ammonium salt enables the polymer to have good bactericidal performance and the quaternized stability of the polymer of the invention is high; the polyurethane system has strong versatility, excellent and adjustable performance, and has a variety of molecular structures with different structures and performances.

[0037] The present invention provides a molecular chain structure of the polymer, wherein a structural unit A or a structural unit B is inserted between two adjacent polyurethane segments, and the two ends of the molecular chain structure of the entire polymer have the acrylate end-capping group, wherein, as the functional structural unit, the structural unit A can provide the molecular chain structure of the polymer with a -SS- group, and the structural unit B can provide the macromolecular chain of the polymer with a structure shown in formula (1).

[0038] In the present invention, the copolymer chain represented by R can be connected through the N element in the structural unit B shown in formula (1), thereby bringing good antibacterial properties to the macromolecular chain structure of the modified polyurethane and preventing the high molecular antibacterial unit from migrating and losing easily.

[0039] In the present invention, the two ends of the structural unit B represented by formula (1) can be connected to different polyurethane segments in the molecular chain structure of the polymer.

[0040] According to a preferred embodiment of the present invention, R2 is selected from -CH3 or -C2H5.

[0041] According to a preferred embodiment of the present invention, Z1 and Z2 are each independently -CH2CH2- or -CH2CH2CH2-.

[0042] According to a preferred embodiment of the present invention, R1 and R3 are each independently a structure represented by the general formula -O-Z1*.

[0043] According to a preferred embodiment of the present invention, R1 and R3 are both -O-CH2CH2*.

[0044] According to a preferred embodiment of the present invention, R 1 Selected from -CH2- or -CH2CH2-.

[0045] According to a preferred embodiment of the present invention, R 2 Selected from -CH3 or -C2H5.

[0046] According to a preferred embodiment of the present invention, X is selected from Cl or Br.

[0047] According to a preferred embodiment of the present invention, the monoolefin is selected from one of isobutylene, isopentene, isohexene, isoheptene and isooctene.

[0048] According to a preferred embodiment of the present invention, the structural unit A has the general formula or In the structure shown in FIG. 1 , Z3, Z4, Z5, and Z6 are each independently a phenylene group or a C1-C6 straight-chain or branched alkylene group. In the structure shown, 1 is connected to SS, and 2 is connected to NH. The two ends of the general formula of the structural unit A can be connected to different polyurethane segments in the molecular chain structure of the modified polyurethane.

[0049] According to a preferred embodiment of the present invention, Z3, Z4, Z5 and Z6 are each independently -CH2CH2- or -C6H4-.

[0050] According to a preferred embodiment of the present invention, the structural unit A has

[0051] The structure shown. -NH- can be substituted at the para-position or meta-position of the benzene ring, preferably at the para-position.

[0052] According to a preferred embodiment of the present invention, the acrylate end-capping group has a structure shown in formula (4),

[0053] R4 is selected from a C1-C5 straight or branched chain alkylene group.

[0054] According to a preferred embodiment of the present invention, R4 is selected from -CH2-, -CH2CH2- or -CH2CH2CH2-.

[0055] According to a preferred embodiment of the present invention, R5 is selected from -H or a C1-C3 straight or branched alkyl group.

[0056] According to a preferred embodiment of the present invention, R5 is selected from -H or -CH3.

[0057] According to a preferred embodiment of the present invention, the polyurethane segment contains a structural unit F derived from a polyisocyanate and a structural unit G derived from an oligomeric polyol.

[0058] In the present invention, the polyisocyanate is selected from a wide range, and all commonly used types can be used in the present invention. According to a preferred embodiment of the present invention, the polyisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate. By adopting the above-mentioned preferred embodiment, the versatility and excellent performance adjustability of polyurethane can be further improved.

[0059] In the present invention, the polyether polyol is selected from a wide range, and commonly used types can be used in the present invention. According to a preferred embodiment of the present invention, the oligomeric polyol is a polyether polyol, preferably selected from at least one of polypropylene glycol-2000, polypropylene glycol-3000, polypropylene glycol-4000, polypropylene glycol-5000 and polypropylene glycol-6000. By adopting the above-mentioned preferred embodiment, the practicality and antibacterial property of the photocurable coating prepared by the present invention can be further improved.

[0060] According to a preferred embodiment of the present invention, the weight average molecular weight of the polyurethane segment is 3200-8000 g / mol.

[0061] According to a preferred embodiment of the present invention, in the structural unit B, the molar ratio of structural unit C:structural unit D is 1:(0.5-0.8).

[0062] According to a preferred embodiment of the present invention, in the structural unit B, the molar ratio of structural unit D:structural unit E is 1:(2-10).

[0063] According to a preferred embodiment of the present invention, the weight average molecular weight of the copolymer is 3000-6000 g / mol.

[0064] According to a preferred embodiment of the present invention, in the functional structural unit, the molar ratio of the structural unit A to the structural unit B is (2-2.5):1.

[0065] According to a preferred embodiment of the present invention, based on the total amount of the polymer, the molar ratio of the polyurethane segment, the functional structural unit and the acrylate end-capping group is 1:(1-1.2):(0.8-1).

[0066] According to a preferred embodiment of the present invention, the weight average molecular weight of the polymer is 8000-15000 g / mol, and the viscosity at 25° C. is 100-400 mPa / s.

[0067] According to a particularly preferred embodiment of the present invention, two adjacent polyurethane segments are connected via the functional structural unit, and the end of the macromolecular chain of the modified polyurethane is the acrylate end-capping group.

[0068] According to a particularly preferred embodiment of the present invention, the macromolecular chain of the modified polyurethane further comprises a connecting group represented by the general formula -NHCO located between the polyurethane segment and the functional structural unit.

[0069] In the present invention, the connecting group may be generated by the reaction of the -NCO group originally present at the end of the polyurethane segment with the -OH or -NH group present at the end of the functional structural unit.

[0070] The second aspect of the present invention provides a method for preparing the polymer of the present invention, the method comprising the following steps:

[0071] (1) in the presence of a catalyst, polyisocyanate and oligomer polyol are subjected to polycondensation reaction to generate a solution A containing polyurethane;

[0072] (2) copolymerizing solution A, an embedded copolymer and a disulfide bond extender to obtain a polymer precursor; the embedded copolymer contains a structural unit D represented by formula (3), a structural unit F represented by formula (5) and a structural unit E derived from a monoolefin,

[0073]

[0074] (3) subjecting the polymer precursor and the end-capping agent to an end-capping reaction to obtain a polymer;

[0075] R1, R2, R3, R, R 2 The definitions of are the same as those described in the polymer of the present invention.

[0076] In the present invention, the disulfide bond extender and the hydroxyl groups embedded in the copolymer react with the -NCO bonds in the polyurethane to achieve linkage with the polyurethane, and the formed polymer precursor is then capped at the ends of the polyurethane segments therein by a capping agent, and the groups of the capping agent are introduced to obtain the polymer.

[0077] The polymer prepared by the method of the present invention has good mechanical properties. The quaternary ammonium copolymer is an antibacterial component, which is connected to the main chain of the polyurethane resin by polymerization through the terminal hydroxyl group, thereby overcoming the problem of seepage or dissolution that is easy to occur when adding a blended antibacterial agent; in addition, the high-molecular antibacterial unit is not easy to migrate and lose, and is safer and less toxic than small-molecule organic antibacterial agents. Therefore, the prepared polymer has low toxicity and good antibacterial properties.

[0078] In one embodiment of the present invention, the pretreatment of isocyanate and the test of isocyanate group content are both carried out using methods commonly used in the art.

[0079] According to a preferred embodiment of the present invention, when the -NCO content in solution A decreases by 50 wt%, step (2) is started.

[0080] According to a preferred embodiment of the present invention, the end point of the end-capping reaction in step (3) is: when the -NCO content in the reaction system is less than or equal to 0.3%, the reaction is stopped and the obtained polymer needs to be cooled to room temperature before being discharged.

[0081] According to a preferred embodiment of the present invention, the molar ratio of the polyisocyanate to the oligomer polyol is (2-2.5):1.

[0082] According to a preferred embodiment of the present invention, the molar ratio of the blocking agent to the polyisocyanate is 1:(2-3.5).

[0083] According to a preferred embodiment of the present invention, the amount of the catalyst used is 0.05-0.1 wt% relative to the total amount of feed.

[0084] According to a preferred embodiment of the present invention, the amount of the disulfide bond extender is 0.5-2.5 wt % relative to the total amount of feed.

[0085] According to a preferred embodiment of the present invention, the amount of the embedded copolymer is 10-22 wt % relative to the total amount of feed.

[0086] According to a preferred embodiment of the present invention, the total amount of the feed is the sum of the respective feed amounts of the polyisocyanate, the oligomeric polyol, the embedded copolymer, the catalyst, the disulfide bond extender and the end-capping agent.

[0087] According to a preferred embodiment of the present invention, the polyisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate.

[0088] According to a preferred embodiment of the present invention, the oligomer polyol is a polyether polyol, preferably at least one selected from polypropylene glycol-2000, polypropylene glycol-3000 and polypropylene glycol-6000, and has a weight average molecular weight of 2000-6000 g / mol.

[0089] In the present invention, the types of the disulfide bond chain extender can be selected from a wide range. According to a preferred embodiment of the present invention, the disulfide bond chain extender is selected from compounds with the general formula HO-Z3-SS-Z4-OH or H2N-Z5-SS-Z6-NH2, wherein Z3, Z4, Z5, and Z6 are each independently a phenylene group or a straight or branched alkylene group of C1-C6, and preferably Z3 and Z4 are each independently -CH2CH2- or -C6H4-.

[0090] According to a particularly preferred embodiment of the present invention, the disulfide bond chain extender is selected from at least one of bis(2-hydroxyethyl) disulfide, 4,4'-disulfodiphenylamine, and 2,2-disulfodiphenylamine. By adopting the above-mentioned preferred embodiment, the disulfide bond chain extender contains a reversible covalent disulfide bond, which can partially or completely restore the mechanical properties and integrity of the polymer itself under the stimulation of external conditions such as light, heat, acid and alkali, and can achieve repair.

[0091] According to a preferred embodiment of the present invention, in the present invention, the type of the capping agent can be selected from a wide range, and commonly used capping agents can be used in the present invention, such as hydroxyl functional acrylate capping agents. According to a preferred embodiment of the present invention, the capping agent has a structure shown in formula (A4),

[0092] Among them, R4 is selected from C1-C5 straight chain or branched alkylene, preferably -CH2-, -CH2CH2-, -CH2CH2CH2-; R5 is selected from -H or, C1-C3 straight chain or branched alkyl, preferably -H or -CH3.

[0093] According to a particularly preferred embodiment of the present invention, the end-capping agent is selected from at least one of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate. Through the above-mentioned preference, the terminal hydroxyl group is polymerized into the main chain of the polyurethane resin, thereby overcoming the problem of seepage or dissolution that is prone to occur when adding a blended antibacterial agent.

[0094] In the present invention, the catalyst has a wide range of optional types, and commonly used catalysts can be used in the present invention. According to a preferred embodiment of the present invention, the catalyst is an organic tin catalyst, preferably at least one of dibutyltin dilaurate and stannous octoate. By adopting the above-mentioned preferred embodiment, the practicality and antibacterial property of the photocurable coating prepared by the present invention can be further improved.

[0095] In the present invention, the embedded copolymer may be a prepared copolymer having the structural units D, F and E. For example, it may be prepared by the following method:

[0096] (i) subjecting a monoolefin and a monomer d providing a structural unit D to a cationic solution polymerization reaction in the presence of an initiator system and a solvent to obtain a binary copolymer solution containing structural units D and structural units E;

[0097] (ii) washing the binary copolymer solution with water and then subjecting it to a halogenation reaction to obtain a halogenated polymer;

[0098] (iii) subjecting the halogenated polymer to a salification reaction with a polyol amine to obtain the embedded copolymer.

[0099] Among them, in (iii), the polyol amine can be bonded to part of the halogenated groups in the halogenated polymer through the N element contained in each of the polyol amines through the salification reaction, thereby forming the structural unit F accordingly.

[0100] According to a preferred embodiment of the present invention, the weight average molecular weight of the embedded copolymer is 3000-6000 g / mol.

[0101] According to a preferred embodiment of the present invention, the monoolefin is selected from one of isobutylene, isopentene, isohexene, isoheptene and isooctene, preferably isobutylene.

[0102] According to a preferred embodiment of the present invention, the amount of monomer d added satisfies that the mass fraction of the structural unit D is 20-40% based on the total weight of the embedded copolymer.

[0103] According to a preferred embodiment of the present invention, the added amounts of monomer d and polyol amine satisfy that in the embedded copolymer, the molar ratio of the structural unit F:structural unit D is 1:(0.5-0.8), for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, or any value in the range consisting of any two of the above values.

[0104] In a preferred embodiment of the present invention, the polyol amine is selected from N-methyldiethanolamine and / or N-methyldipropanolamine.

[0105] The monomer e is selected from one of p-methylstyrene, p-ethylstyrene and p-isobutylstyrene.

[0106] In a particularly preferred embodiment of the present invention, preferably, the polyol amine is N-methyldiethanolamine, the monomer e is p-methylstyrene, the monoolefin is isobutylene, and the halogenation reaction is a bromination reaction.

[0107] The monoolefin and the monomer d providing the structural unit D are subjected to cationic solution polymerization to obtain a binary copolymer containing the structural unit D and the structural unit E.

[0108] There is no particular limitation on the initiator system described in (i), as long as it can promote the cationic polymerization reaction of the monoolefin and the monomer e. For example, the initiator system contains a compound capable of providing protons (such as HCl), at least one Lewis acid (ethylaluminum dichloride, diethylaluminum chloride) and at least one activator (such as tetrahydrobenzoquinone, tetrachlorobenzoquinone, tetracyanobenzoquinone and dichlorodicyanobenzoquinone). In the present invention, hydrogen chloride / ethylaluminum dichloride / tetrachlorobenzoquinone is used as the initiator system (the molar concentration ratio is 1:10:1) to exemplify the advantages of the present invention. However, the present invention is not limited thereto; the solvent may be an alkane or a halogenated alkane. In the present invention, hexane / dichloromethane (60 / 40, V / V) is used as a solvent to exemplify the advantages of the present invention, but the present invention is not limited thereto; there is no special restriction on the amount of solvent and initiator in the initiator system, and those skilled in the art may select them according to their needs, and no further details are given here; wherein, the conditions of the solution polymerization reaction include: the solution polymerization is carried out at a temperature in the range of -60°C to -20°C to prepare a medium-low molecular weight fully saturated binary copolymer containing structural unit D and structural unit E. The cationic solution polymerization reaction is carried out between monomer d and the olefin carbon-carbon double bond in the monoolefin. wherein, monomer d provides the structural unit D.

[0109] (ii) The binary copolymer undergoes the halogenation reaction with halogen, wherein the conditions of the halogenation reaction include: washing the binary copolymer solution with water, and then performing a pulse (10s) photobromination reaction at room temperature by slowly adding liquid bromine with a 595nm light source, the bromination reaction time is 100-150min, and then washing the brominated gel solution with water and centrifuging to obtain a halogenated polymer; R in some structural units D can be 2 The halogen is substituted to form a halogenated side group in the macromolecular chain of the binary copolymer.

[0110] The conditions of the salification reaction in (iii) include: a reaction temperature of 50-80°C and a reaction time of 12-24 hours. After the reaction is completed, a certain amount of anhydrous ether is added to the system, and a large amount of solid is precipitated. After filtering, washing and drying, the embedded copolymer is obtained. The polyol amine reacts with the halogenated side group through the N element contained therein to form the structural unit F in the embedded copolymer accordingly.

[0111] In the present invention, further, the hydroxyl group introduced into the structural unit F through the polyol amine can react with the isocyanate group contained in the polyurethane contained in the solution A during the copolymerization reaction of step (2) to form a connection shown in -NHCO-.

[0112] In the present invention, the disulfide bond extender reacts with the isocyanate group contained in the polyurethane contained in the solution A to form a connection shown as -NHCO- through the hydroxyl group or amino group contained in the disulfide bond extender during the copolymerization reaction of step (2).

[0113] In the present invention, through the copolymerization reaction in step (2), the embedded copolymer and the disulfide bond chain extender are respectively introduced into the macromolecular chain of the polyurethane.

[0114] According to a preferred embodiment of the present invention, the conditions of the polycondensation reaction include: reaction time: 1-2h, reaction temperature: 60-70°C.

[0115] According to a preferred embodiment of the present invention, the conditions of the copolymerization reaction include: reaction time: 2-4h, reaction temperature: 70-80°C.

[0116] According to a preferred embodiment of the present invention, the conditions of the end-capping reaction include: reaction time: 1-2h, reaction temperature: 80-85°C. The terminal hydroxyl group contained in the end-capping agent reacts with the isocyanate terminal group in the polymer precursor, and the isocyanate terminal group is converted into the terminal group provided by the end-capping agent by forming an -NHCO- group, thereby overcoming the problem of exudation or dissolution that is prone to occur when adding a blended antimicrobial agent.

[0117] The third aspect of the present invention provides a polymer obtained by the preparation method of the present invention.

[0118] The polymer provided by the invention has good mechanical properties, antibacterial properties and stability.

[0119] A fourth aspect of the present invention provides a self-repairing antibacterial photocurable coating composition, which contains the polymer described in the present invention.

[0120] The present invention provides a self-repairing antibacterial cured coating film containing the polymer of the present invention, which can improve the antibacterial property, mechanical property and self-repairing property of the self-repairing antibacterial cured coating film.

[0121] According to a preferred embodiment of the present invention, the composition further contains a reactive diluent and a photoinitiator.

[0122] According to a preferred embodiment of the present invention, based on the total amount of the composition, the polymer comprises 40-55 parts, the reactive diluent comprises 42-55 parts, and the photoinitiator comprises 3-5 parts.

[0123] A fifth aspect of the present invention provides an application of the polymer described in the present invention in a self-repairing antibacterial cured coating.

[0124] By applying the polymer prepared by the present invention to a self-repairing antibacterial cured coating, the antibacterial property, mechanical properties and self-repairing property of the coating can be improved.

[0125] A sixth aspect of the present invention provides a method for preparing a self-repairing antibacterial photocurable coating film, the preparation method comprising the following steps:

[0126] (1) mixing a polymer, a reactive diluent, and a photoinitiator to obtain a mixture A;

[0127] (2) Curing the mixture A to obtain a self-repairing antibacterial photocured coating.

[0128] According to a preferred embodiment of the present invention, the polymer is the polymer described in the present invention.

[0129] The photocuring technology provided by the method of the present invention has outstanding advantages in preparing antibacterial polymer film coatings. The method has mild reaction conditions, fast reaction speed and high efficiency, which is beneficial to maintaining the activity of antibacterial groups and avoids the disadvantages of loss of antibacterial activity caused by traditional thermal polymerization and its processing process. It is green, environmentally friendly and highly practical.

[0130] In the present invention, the types of the reactive diluent can be selected from a wide range, and all commonly used types can be used in the present invention. According to a preferred embodiment of the present invention, the reactive diluent is selected from at least one of tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane trimethacrylate and isobornyl acrylate. By adopting the above-mentioned preferred embodiment, the reactive diluent is used as a reactive diluent for the photocurable coating, and the multiple active functional groups of the reactive diluent can participate in the reaction, thereby not only improving the curing rate of the photocurable coating, but also improving the comprehensive performance of the material.

[0131] According to a preferred embodiment of the present invention, the reactive diluent is selected from at least one of tripropylene glycol diacrylate, 1,6-hexanediol diacrylate and isobornyl acrylate. By adopting the above-mentioned preferred embodiment, the reactive diluent is used as a reactive diluent for the photocurable coating, and the multiple reactive functional groups of the reactive diluent can participate in the reaction, thereby not only improving the curing rate of the photocurable coating, but also improving the comprehensive performance of the material.

[0132] According to a preferred embodiment of the present invention, the mass ratio of tripropylene glycol diacrylate, 1,6-hexanediol diacrylate and isobornyl acrylate is (12-20):(10-15):(15-25).

[0133] According to a preferred embodiment of the present invention, the photoinitiator is selected from at least one of 1-hydroxycyclohexyl benzophenone, 2-hydroxy-2-methyl-1-phenylacetone and (2,4,6-trimethylbenzoyl) diphenylphosphine oxide. By adopting the above-mentioned preferred embodiment, the absorption spectrum of the photoinitiator matches the emission spectrum of the radiation light source, which can efficiently induce the chemical reaction between the unsaturated double bonds in the system and improve the photoinitiation efficiency.

[0134] According to a preferred embodiment of the present invention, the photoinitiator is selected from 2-hydroxy-2-methyl-1-phenylpropanone. By adopting the above-mentioned preferred embodiment, the absorption spectrum of the photoinitiator matches the emission spectrum of the radiation light source, which can effectively induce the chemical reaction between the unsaturated double bonds in the system and improve the photoinitiation efficiency.

[0135] According to a particularly preferred embodiment of the present invention, the curing machine has a power of 1000-1500 W, a main emission wavelength of 365 nm and 385 nm, and an irradiation distance of 20-25 cm.

[0136] According to a preferred embodiment of the present invention, the mixing conditions include: the reaction temperature is 30-60°C.

[0137] According to a preferred embodiment of the present invention, the mixing conditions include: the reaction time is 2-5h.

[0138] According to a preferred embodiment of the present invention, the curing conditions include: temperature of 20-30° C. and time of 1-10 min.

[0139] According to a preferred embodiment of the present invention, in parts by weight, the polymer comprises 40-55 parts, the reactive diluent comprises 42-55 parts, and the photoinitiator comprises 3-5 parts.

[0140] The seventh aspect of the present invention provides a self-repairing antibacterial photocured coating film prepared by the preparation method described in the present invention.

[0141] The self-repairing antibacterial photocured coating prepared by the present invention has excellent antibacterial properties and self-repairing properties.

[0142] An eighth aspect of the present invention provides an application of the self-repairing antibacterial photocuring coating film described in the present invention in surface finishing of public goods.

[0143] The self-repairing antibacterial photocuring coating prepared by the present invention is applied to the surface of public goods to make them have excellent antibacterial properties.

[0144] A ninth aspect of the present invention provides a product having the self-repairing antibacterial photocured coating film of the present invention on its surface.

[0145] In order to make the present invention easier to understand, the present invention will be described in detail below in conjunction with examples. These examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The raw materials involved in the examples are all commercially available unless otherwise specified. The composition structure of the obtained polymer is determined by feeding.

[0146] Self-repair efficiency: The sample is divided into two parts, one part is cut from the middle with scissors, the two parts are tightly fitted and placed in a 50℃ oven for 2 hours, and the other part is the original sample without any treatment. The tensile strength of the repaired sample and the original sample after 2 hours is tested respectively and their self-repair efficiency is calculated. Among them, the self-repair efficiency H is the ratio of the tensile strength of the repaired sample to the tensile strength of the original sample.

[0147] Antibacterial performance test: The antibacterial effect of the antibacterial coating was tested according to ISO 22196 standard. The experimental object was Gram-negative bacteria Escherichia coli. The plate count method was used to test the antibacterial rate of the coating against Escherichia coli at different times. The whole process was carried out under sterile operation.

[0148] Water absorption rate: Cut the membrane into 25mm×25mm slices, dry them in an oven at 60℃ for 24h, weigh them as W1, and then place the dried slices in 50mL deionized water for 24h, absorb the unabsorbed water on the surface, weigh them as W2, then the water absorption rate = (W2-W1 / W1)×100%.

[0149] The molecular weight of the polymer was determined by using an LC-20A gel permeation chromatograph, with tetrahydrofuran as solvent, a sample concentration of 20 mg / 10 mL, an injection volume of 100 μL, a flow rate of 1.0 mL / min, and a calibration curve determined using PS as the standard.

[0150] Viscosity: Use a digital rotational viscometer and select a suitable rotor to measure the viscosity of the sample at various temperatures. The resin must flow over the rotor.

[0151] Preparation Example

[0152] For illustration of the preparation of embedded copolymers:

[0153] Using hydrogen chloride / ethylaluminum dichloride / tetrachlorobenzoquinone (the molar concentration ratio is 1:10:1) as the initiation system and hexane / dichloromethane (60 / 40, V / V) as the solvent, isobutylene and p-methylstyrene are subjected to cationic solution polymerization reaction in the range of -60°C to -20°C to obtain an isobutylene-p-methylstyrene copolymer solution;

[0154] After washing the isobutylene-p-methylstyrene copolymer solution with water, the isobutylene-p-methylstyrene copolymer solution is subjected to a photobromination reaction by slowly dropping liquid bromine at room temperature and under the condition of 595 nm light source pulse (10 s) irradiation. The bromination reaction time is 60-150 min. The obtained product is washed with water and centrifuged for dehydration to obtain a brominated polymer.

[0155] N-methyldiethanolamine and brominated polymer are subjected to salification reaction at a reaction temperature of 50-80°C for 10-24 hours. After the reaction is completed, a certain amount of anhydrous ether is added to the system, and a large amount of solid is precipitated. After filtering, washing, and drying, the embedded copolymer is obtained, and its schematic structure is shown below:

[0156] Adjust the conditions and the amount of raw materials added to obtain:

[0157] Embedded copolymer I: weight average molecular weight 3200 g / mol, mass fraction of structural unit D is 25%, molar ratio of structural unit F: structural unit D is 1:0.5;

[0158] Embedded copolymer II: weight average molecular weight 3000 g / mol, mass fraction of structural unit D is 25%, molar ratio of structural unit F: structural unit D is 1:0.7;

[0159] Embedded copolymer III: weight average molecular weight 5100 g / mol, mass fraction of the structural unit D is 40%, and the molar ratio of structural unit F: structural unit D is 1:0.6;

[0160] Embedded copolymer IV: weight average molecular weight 6000 g / mol, mass fraction of structural unit D is 20%, molar ratio of structural unit F:structural unit D is 1:0.8.

[0161] Example 1

[0162] A thermometer and a constant pressure dropping funnel were placed in a three-necked flask, and 4.44 g of pretreated isophorone diisocyanate was added thereto. Subsequently, 0.02 g of dibutyltin dilaurate as a catalyst was added and stirred evenly. Then, 30.07 g of oligopropylene glycol PPG3000 was slowly added dropwise. After the addition was completed, the temperature was raised to 60°C and the reaction was carried out for 1 hour to generate a solution A containing polyurethane with a weight-average molecular weight of 4000 g / mol. Samples were continuously taken during the reaction process, and the isocyanate group content in the system was determined.

[0163] When the isocyanate group content was reduced to half of the original, 6.31 g of embedded copolymer I and 0.62 g of disulfide chain extender bis(2-hydroxyethyl) disulfide were added to the polyurethane solution A, the temperature was raised to 80°C and the reaction was continued for 1 hour, and finally 1.04 g of hydroxyethyl methacrylate was added dropwise for end-capping, and the reaction was continued at 80°C for 1 hour. During the reaction, samples were continuously taken and the isocyanate group content in the system was measured. When the content was less than 0.3%, the reaction was terminated, the solution was cooled to room temperature, and the material was discharged. The resulting viscous liquid was polymer A1, with a weight average molecular weight of 8500 g / mol and a viscosity of 130 mPa·s at 25°C.

[0164] Example 2

[0165] A thermometer and a constant pressure dropping funnel were placed in a three-necked flask, and 4.44 g of pretreated isophorone diisocyanate was added thereto. Subsequently, 0.02 g of dibutyltin dilaurate as a catalyst was added and stirred evenly. Then, 30.07 g of oligopropylene glycol PPG3000 was slowly added dropwise. After the addition was completed, the temperature was raised to 60°C and the reaction was carried out for 1 hour to generate a solution A containing polyurethane with a weight-average molecular weight of 4000 g / mol. Samples were continuously taken during the reaction process, and the isocyanate group content in the system was determined.

[0166] When the isocyanate group content was reduced to half of the original, 6.31 g of embedded copolymer II and 0.62 g of disulfide chain extender bis(2-hydroxyethyl) disulfide were added to the polyurethane-containing solution A, the temperature was raised to 80°C and the reaction was continued for 1 hour, and finally 1.04 g of hydroxyethyl methacrylate was added dropwise for end-capping, and the reaction was continued at 80°C for 1 hour. During the reaction, samples were continuously taken and the isocyanate group content in the system was measured. When the content was less than 0.3%, the reaction was terminated, the solution was cooled to room temperature, and the material was discharged. The resulting viscous liquid was polymer A2, with a weight average molecular weight of 8700 g / mol and a viscosity of 140 mPa·s at 25°C.

[0167] Example 3

[0168] A thermometer and a constant pressure dropping funnel were placed in a three-necked flask, and 3.48 g of pretreated toluene diisocyanate was added thereto. Subsequently, 0.02 g of dibutyltin dilaurate as a catalyst was added and stirred evenly. Then, 20.01 g of oligopropylene glycol PPG2000 was slowly added dropwise. After the addition was completed, the temperature was raised to 60°C and the reaction was carried out for 2 hours to generate a solution A containing polyurethane with a weight-average molecular weight of 3200 g / mol. Samples were continuously taken during the reaction process, and the isocyanate group content in the system was determined.

[0169] When the isocyanate group content was reduced to half of the original, 7.02 g of embedded copolymer III and 0.54 g of disulfide chain extender bis(2-hydroxyethyl) disulfide were added to the polyurethane-containing solution A, the temperature was raised to 80°C and the reaction was continued for 2 h, and finally 1.20 g of hydroxyethyl acrylate was added dropwise for end-capping, and the reaction was continued at 80°C for 2 h. During the reaction, samples were continuously taken and the isocyanate group content in the system was measured. When the content was less than 0.3%, the reaction was terminated, the solution was cooled to room temperature, and the material was discharged. The resulting viscous liquid was polymer A3, with a weight average molecular weight of 9000 g / mol and a viscosity of 200 mPa s at 25°C.

[0170] Example 4

[0171] A thermometer and a constant pressure dropping funnel were placed in a three-necked flask, and 3.48 g of pretreated toluene diisocyanate was added thereto. Subsequently, 0.02 g of dibutyltin dilaurate as a catalyst was added and stirred evenly. Then, 20.01 g of oligopropylene glycol PPG2000 was slowly added dropwise. After the addition was completed, the temperature was raised to 60°C and the reaction was carried out for 2 hours to generate a solution A containing polyurethane with a weight-average molecular weight of 3200 g / mol. Samples were continuously taken during the reaction process, and the isocyanate group content in the system was determined.

[0172] When the isocyanate group content was reduced to half of the original, 7.02 g of embedded copolymer IV and 0.54 g of disulfide chain extender bis(2-hydroxyethyl) disulfide were added to the polyurethane-containing solution A, the temperature was raised to 80°C and the reaction was continued for 2 h, and finally 1.20 g of hydroxyethyl acrylate was added dropwise for end-capping, and the reaction was continued at 80°C for 2 h. During the reaction, samples were continuously taken and the isocyanate group content in the system was measured. When the content was less than 0.3%, the reaction was terminated, the solution was cooled to room temperature, and the material was discharged. The resulting viscous liquid was polymer A4, with a weight average molecular weight of 9500 g / mol and a viscosity of 220 mPa s at 25°C.

[0173] Example 5

[0174] A thermometer and a constant pressure dropping funnel were placed in a three-necked flask, and 4.01 g of pretreated toluene diisocyanate was added thereto. Subsequently, 0.06 g of dibutyltin dilaurate as a catalyst was added and stirred evenly. Then, 60.02 g of oligopropylene glycol PPG6000 was slowly added dropwise. After the addition was completed, the temperature was raised to 60°C and the reaction was carried out for 2 hours to generate a solution A containing polyurethane with a weight-average molecular weight of 7100 g / mol. Samples were continuously taken during the reaction process, and the isocyanate group content in the system was determined.

[0175] When the isocyanate group content was reduced to half of the original, 12.66 g of embedded copolymer IV and 0.65 g of disulfide chain extender bis(2-hydroxyethyl) disulfide were added to the polyurethane-containing solution A, the temperature was raised to 80°C and the reaction was continued for 2 h, and finally 0.95 g of hydroxyethyl acrylate was added dropwise for end-capping, and the reaction was continued at 80°C for 2 h. During the reaction, samples were continuously taken and the isocyanate group content in the system was measured. When the content was less than 0.3%, the reaction was terminated, the solution was cooled to room temperature, and the material was discharged. The resulting viscous liquid was polymer A5, with a weight average molecular weight of 15,000 g / mol and a viscosity of 380 mPa s at 25°C.

[0176] Comparative Example 1

[0177] The same as Example 1, except that no embedded copolymer was added and other reaction conditions remained unchanged. The obtained viscous liquid was polyurethane oligomer D1, with a weight average molecular weight of 4200 g / mol and a viscosity of 94 mPa s at 25°C.

[0178] Comparative Example 2

[0179] The same as Example 1, except that the disulfide bond extender bis(2-hydroxyethyl) disulfide was not added, and other reaction conditions remained unchanged. The obtained viscous liquid was the polyurethane oligomer D2, with a weight average molecular weight of 8000 g / mol and a viscosity of 110 mPas at 25°C.

[0180] Comparative Example 3

[0181] The same as Example 1, except that hydroxyethyl methacrylate was not added, other reaction conditions remained unchanged, and the disulfide bond extender was added and the reaction was continued at 80°C for 1 hour before the reaction was terminated. Since hydroxyethyl methacrylate was not added, the -NCO content in the polymer was always higher than 0.3%. The viscous liquid finally obtained was the polyurethane oligomer D3, with a weight average molecular weight of 7600 g / mol and a viscosity of 100 mPas at 25°C.

[0182] Preparation Example 1-10

[0183] In parts by weight, all raw materials are weighed according to the ratio in Table 1, and the synthesized polyurethane oligomer, active diluent, and photoinitiator are added to the container respectively, and magnetically stirred under light-proof conditions until the mixture is evenly mixed to obtain a mixture A; then, it is evenly coated on the tin-plated tinplate sheet with a wire rod coater, and the thickness of the cured layer is controlled to be 0.4 mm, and placed in a UV curing machine for photocuring to obtain a photocured coating. Wherein, the stirring conditions include: the stirring temperature is 40°C and the stirring time is 3h. The power of the photocuring machine is 1300W, the main emission wavelength is 365nm and 385nm, the irradiation distance is 25cm, the temperature is 25°C, and the time is 4-5min. The photocured coating is configured according to the formula shown in Table 1.

[0184] Table 1

[0185]

[0186] Test Case

[0187] The properties of the photocurable coatings of the above-mentioned Preparation Examples 1-10 were tested, and the results are shown in Table 2.

[0188] Table 2

[0189]

[0190]

[0191] It can be seen from Table 2 that the photocurable coatings obtained in Preparation Examples 1-6, 9, and 10 of the present invention contain reversible covalent disulfide bonds, and are repairable under external conditions such as heating, and the self-repair rate of fractures in 2 hours is greater than 95%. However, the photocurable film obtained in Preparation Example 7 does not contain reversible covalent disulfide bonds, and the self-repair rate of fractures in 2 hours is only 31.8%. Preparation Example 8 does not add an acrylate-based end-capping agent, and the end of the polymer molecular chain does not contain an active site for photoreaction with an active diluent, so the photocurable coating has poor film-forming properties and a low self-repair rate of fractures. In addition, the quaternized isobutylene / p-methylstyrene copolymer is used as an antibacterial component, and the terminal hydroxyl group is polymerized into the main chain of the polyurethane resin, which overcomes the problem of exudation or dissolution that is prone to occur when adding a blended antibacterial agent, and can well protect the bactericidal unit, with good bactericidal performance. The anti-E. coli rate of the photocured films obtained from Preparation Examples 1-5 and Preparation Examples 7-9 was over 45% after 1 hour of contact, and was as high as over 98% after 3 hours of contact. However, the anti-E. coli rate of the photocured film obtained from Preparation Example 6 was only 20.6% after 1 hour of contact, and was 15.4% after 3 hours of contact, indicating that the quaternary ammonium salt makes the photocured film prepared by the present invention have an antibacterial effect.

[0192] The water absorption rate of the coating film is measured to determine its water absorption and hydrolytic stability. As shown in Preparation Example 6, the coating film without the quaternary ammonium salt antibacterial unit has a certain hydrophobicity and is not easy to absorb water and dissolve. The data of Preparation Examples 2 and 9, Preparation Examples 5 and 10 in Table 2 show that as the quaternary ammonium salt component increases, the water absorption rate will also increase accordingly, which is the result that the quaternary ammonium salt cation is easy to bind water.

[0193] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polymer, characterized in that The polymer comprises a polyurethane segment, a functional structural unit and an acrylate end-capping group; wherein the functional structural unit comprises a structural unit A having a -SS- group and a structural unit B represented by formula (1); Wherein, R2 is a C1-C6 straight chain or branched alkyl group, R1 and R3 are each independently a structure represented by the general formula -O-Z1* or -NH-Z2*, wherein Z1 and Z2 are each independently a C1-C6 straight chain or branched alkylene group, R is a copolymer chain containing a structural unit C represented by formula (2), a structural unit D represented by formula (3) and a structural unit E derived from a monoolefin, Among them, R 1 is selected from a C1-C6 straight or branched alkylene group, R 2 is selected from -H or a C1-C6 straight or branched alkyl group, * is the position connecting to the N element in formula (1); X is selected from F, Cl, Br or I.

2. The polymer according to claim 1, wherein R2 is selected from -CH3 or -C2H5; and / or, Z1 and Z2 are each independently -CH2CH2- or -CH2CH2CH2-, preferably R1 and R3 are each independently a structure represented by the general formula -O-Z1*, more preferably R1 and R3 are both -O-CH2CH2*; and / or, R 1 Selected from -CH2- or -CH2CH2-; and / or, R 2 Selected from -CH3 or -C2H5; and / or, X is Cl or Br; And / or, the monoolefin is selected from one of isobutylene, isopentene, isohexene, isoheptene and isooctene.

3. The polymer according to claim 1 or 2, wherein The structural unit A has the general formula The structure shown, wherein Z3, Z4, Z5, and Z6 are each independently phenylene or a C1-C6 straight-chain or branched alkylene; Preferably, Z3, Z4, Z5, and Z6 are each independently -CH2CH2- or -C6H4-; Preferably, the structural unit A has The structure shown.

4. The polymer according to any one of claims 1 to 3, wherein The acrylate end-capping group has a structure shown in formula (4), Wherein, R4 is selected from a C1-C5 straight or branched alkylene group, preferably -CH2-, -CH2CH2- or -CH2CH2CH2-; And / or, R5 is selected from -H or C1-C3 straight chain or branched alkyl, preferably -H or -CH3.

5. The polymer according to any one of claims 1 to 4, wherein The polyurethane segment contains a structural unit F derived from a polyisocyanate and a structural unit G derived from an oligomeric polyol; Preferably, the polyisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate; Preferably, the oligomeric polyol is a polyether polyol, preferably at least one of polypropylene glycol-2000, polypropylene glycol-3000, polypropylene glycol-4000, polypropylene glycol-5000 and polypropylene glycol-6000; Preferably, the weight average molecular weight of the polyurethane segment is 3200-8000 g / mol.

6. The polymer according to any one of claims 1 to 5, wherein In the structural unit B, the molar ratio of structural unit C:structural unit D is 1:(0.5-0.8); The molar ratio of structural unit D: structural unit E is 1:(2-10); Preferably, the weight average molecular weight of the copolymer is 3000-6000 g / mol.

7. The polymer according to any one of claims 1 to 6, wherein In the functional structural unit, the molar ratio of the structural unit A to the structural unit B is (2-2.5):

1.

8. The polymer according to any one of claims 1 to 7, wherein Based on the total amount of the polymer, the molar ratio of the polyurethane segment, the functional structural unit and the acrylate end-capping group is 1:(1-1.2):(0.8-1); Preferably, the weight average molecular weight of the polymer is 8000-15000 g / mol, and the viscosity at 25° C. is 100-400 mPa·s.

9. A method for preparing a polymer, characterized in that: The method comprises the following steps: (1) in the presence of a catalyst, polyisocyanate and oligomer polyol are subjected to polycondensation reaction to generate a solution A containing polyurethane; (2) copolymerizing solution A, an embedded copolymer and a disulfide bond extender to obtain a polymer precursor; wherein the embedded copolymer contains a structural unit D represented by formula (3), a structural unit F represented by formula (5) and a structural unit E derived from a monoolefin, (3) subjecting the polymer precursor and the end-capping agent to an end-capping reaction to obtain a polymer; Among them, R1, R2, R3, R, R 2 The definition is the same as that in claim 1.

10. The preparation method according to claim 9, wherein: The molar ratio of the polyisocyanate to the oligomer polyol is (2-2.5):1; and / or The molar ratio of the blocking agent to the polyisocyanate is 1:(2-3.5); and / or Relative to the total amount of feed: The amount of the catalyst is 0.05-0.1wt%; and / or The disulfide bond extender is used in an amount of 0.5-2.5 wt %; and / or The amount of the embedded copolymer is 10-22wt%; The total amount of the feed is the sum of the polyisocyanate, the oligomeric polyol, the embedded copolymer, the catalyst, the disulfide bond chain extender and the end-capping agent.

11. The preparation method according to claim 9 or 10, wherein: The polyisocyanate is at least one of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate; Preferably, the oligomer polyol is a polyether polyol, preferably at least one of polypropylene glycol-2000, polypropylene glycol-3000 and polypropylene glycol-6000, with a weight average molecular weight of 2000-6000 g / mol; Preferably, the disulfide bond extender is selected from compounds having the general formula HO-Z3-SS-Z4-OH or H2N-Z5-SS-Z6-NH2, wherein Z3, Z4, Z5, and Z6 are each independently a phenylene group or a C1-C6 straight chain or branched alkylene group, preferably Z3 and Z4 are each independently -CH2CH2- or -C6H4-, and further preferably, the disulfide bond extender is selected from at least one of bis(2-hydroxyethyl) disulfide, 4,4'-dithiodiphenylamine, and 2,2-dithiodiphenylamine; Preferably, the end-capping agent has a structure shown in formula (A4), Wherein, R4 is selected from C1-C5 straight chain or branched alkylene, preferably -CH2-, -CH2CH2-, -CH2CH2CH2-; R5 is selected from -H or C1-C3 straight chain or branched alkyl, preferably -H or -CH3, and it is further preferred that the end-capping agent is selected from at least one of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate; Preferably, the catalyst is an organic tin catalyst, preferably at least one of dibutyltin dilaurate and stannous octoate.

12. The preparation method according to any one of claims 9 to 11, wherein: The weight average molecular weight of the embedded copolymer is 3000-6000 g / mol; Preferably, the monoolefin is selected from one of isobutylene, isopentene, isohexene, isoheptene and isooctene, preferably isobutylene; Preferably, based on the total weight of the embedded copolymer, the mass fraction of the structural unit D is 20-40%; Preferably, the molar ratio of the structural unit F:structural unit D is 1:(0.5-0.8).

13. The preparation method according to any one of claims 9 to 12, wherein: The conditions of the polycondensation reaction include: reaction time: 1-2h, reaction temperature: 60-70°C; Preferably, the copolymerization reaction conditions include: reaction time: 2-4h, reaction temperature: 70-80°C; Preferably, the conditions for the end-capping reaction include: reaction time: 1-2h, reaction temperature: 80-85°C.

14. A polymer obtained by the preparation method according to any one of claims 9 to 13.

15. A self-repairing antibacterial photocurable coating composition, comprising the polymer according to any one of claims 1 to 8 and 14; Preferably, the composition further contains a reactive diluent and a photoinitiator; Preferably, based on the total amount of the composition, the polymer comprises 40-55 parts, the reactive diluent comprises 42-55 parts, and the photoinitiator comprises 3-5 parts.

16. Use of the polymer according to any one of claims 1 to 8 and 14 in a self-repairing antibacterial curing coating.

17. A method for preparing a self-repairing antibacterial light-cured coating, characterized in that: The preparation method comprises the following steps: (1) mixing a polymer, a reactive diluent, and a photoinitiator to obtain a mixture A; (2) Curing the mixture A to obtain a self-repairing antibacterial photocured coating.

18. The preparation method according to claim 17, wherein: The reactive diluent is selected from at least one of tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane trimethacrylate and isobornyl acrylate, preferably selected from tripropylene glycol diacrylate, 1,6-hexanediol diacrylate and isobornyl acrylate; Preferably, the mass ratio of tripropylene glycol diacrylate, 1,6-hexanediol diacrylate and isobornyl acrylate is (12-20):(10-15):(15-25); Preferably, the photoinitiator is selected from at least one of 1-hydroxycyclohexyl benzophenone, 2-hydroxy-2-methyl-1-phenylpropanone and (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, preferably 2-hydroxy-2-methyl-1-phenylpropanone.

19. The preparation method according to claim 17 or 18, wherein: The mixing conditions include: reaction temperature of 30-60°C, reaction time of 2-5h; and / or The curing conditions include: temperature of 20-30° C. and time of 1-10 min.

20. The preparation method according to any one of claims 17 to 19, wherein: In parts by weight, the polymer comprises 40-55 parts, the active diluent comprises 42-55 parts, and the photoinitiator comprises 3-5 parts.

21. A self-repairing antibacterial photocured coating film obtained by the preparation method according to any one of claims 17 to 20.

22. Use of the self-repairing antibacterial photocurable coating film according to claim 21 in surface finishing of public goods.

23. A product having the self-repairing antibacterial photocured coating according to claim 21 on its surface.

Citation Information

Patent Citations

  • Self-repairing linear polyurethane elastomer and preparation method thereof

    CN108864403A

  • Disulfide bond and hydrogen bond-containing double self-repairing polyurethane coating for invisible car clothing and preparation method thereof

    CN110591542A

  • Self-repairing waterborne polyurethane-polyacrylic acid emulsion and preparation method thereof

    CN112409547A

  • Blood environment self-repairing polyurethane elastomer as well as preparation method and application thereof

    CN116023613A

  • Self-repairing antibacterial waterborne polyurethane as well as preparation method and application thereof

    CN116478361A